2016
DOI: 10.1007/s13679-016-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

Satiety and the Self-Regulation of Food Take in Children: a Potential Role for Gene-Environment Interplay

Abstract: Child eating self-regulation refers to behaviors that enable children to start and stop eating in a manner consistent with maintaining energy balance. Perturbations in these behaviors, manifesting as poorer child eating self-regulation, are associated with higher child weight status. Initial research into child eating self-regulation focused on the role of parent feeding styles and behaviors. However, we argue that child eating self-regulation is better understood as arising from a complex interplay between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 66 publications
1
23
0
5
Order By: Relevance
“…A poor eating self-regulation in children has been associated with higher body weight ( Hughes and Frazier-Wood, 2016 ). Picky eating is common in preschool children, which leads to parental anxiety and family conflicts ( Kumar et al, 2018 ).…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…A poor eating self-regulation in children has been associated with higher body weight ( Hughes and Frazier-Wood, 2016 ). Picky eating is common in preschool children, which leads to parental anxiety and family conflicts ( Kumar et al, 2018 ).…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…Related to the broader concept of self-regulation is eating-related self-regulation, or the ability to begin and end an eating event in response to internal cues of hunger and fullness 63 . While the extent to which these two constructs are related has been debated, it has been suggested that eating self-regulation is a domain-specific manifestation of broader self-regulatory capacity 64 . Based on this apparent relationship, we might expect to see better eating self-regulation in female relative to male children.…”
Section: Evidence Of Sex-effects On Eating Self-regulation In Childrenmentioning
confidence: 99%
“…Perhaps the biggest moderator of children's eating behaviours is the early food environment, which includes the foods children come into contact with and interactions with parents, family and caregivers. These are unique to each child and interact with a genetic predisposition to excess weight gain to impact individual trajectories in the development of eating behaviours and growth outcomes (Hughes & Frazier‐Wood ; Kral et al . ).…”
Section: Learning To Eat and Influences From The Early Food Environmementioning
confidence: 99%
“…Outside of the area of appetite control, self‐regulation refers to the control of thoughts and behaviours in a way that is adaptive to the changing demands of the external environment, including responding to caregiver actions, expectations and requests (Kopp ). This is underpinned by factors related to language acquisition and executive functioning, which rely on the development of working memory, attention and inhibitory control and have been independently linked to child BMI (see Hughes & Frazier‐Wood ). Importantly, the early expression of these cognitive systems and processes only starts to consolidate after the first few years of life and continue to develop throughout childhood and adolescence (McClelland et al .…”
Section: Learning To Eat and Influences From The Early Food Environmementioning
confidence: 99%
See 1 more Smart Citation